SWALLOW HABI-TECH : PENANGKARAN DAN GALERI WALET DI KARST CIAMPEA, BOGOR, INDONESIA - Maria Stefani; Alvin Hadiwono (Jurusan Arsitektur dan Perencanaan, 2021)
Global warming is a common problem that occurs in all parts of the world that triggers significant climate changes such as temperature increases, humidity changes, natural disasters, and can cause the extinction of flora and fauna, one of which is the swallow in Ciampea Karst, which has been damaged so that uninhabitable. In addition, the exploitation of limestone caves by humans causes swallows to feel uncomfortable and the need for artificial habitats. The goal is that the swallow's need for replacement habitat is fulfilled so that the Ciampea Karst ecosystem is not disturbed. The resulting architectural form is a technology-based captivity that takes swallows as the main subject of the project. The method used begins with the phenomenon and urgency of swallows that occur in Ciampea Karst area. Then analyzed and generated ideas in the form of captivity. However, it is not only limited to captivity, there is also an interaction space for humans in the form of swallow galleries, so that visitors can see the swallow's life. The overall shape of the building is based on an analysis study of the shape of the swallow's flying movement, so that the building adapts many forms of arches that are flexible in accordance with the swallow's daily activities. For the breeding method, it begins by using adaptation techniques first, namely by breeding the seriti bird that takes care of swallow eggs taken from the limestone caves of the Ciampea Karst. In addition to methods in design, the use of technology in building materials, especially in captivity and galleries, also uses natural materials such as natural exposed wood and brick walls. So, to show the side 'beyond ecology', it is not only limited to ecology in the use of materials, but there is an indirect interaction space between humans and swallows that functions to fight against human anthropocentric attitudes, while helping humans to feel the swallow's life in an architectural building. Keywords: captivity; gallery; habitat; technology; white swallow. AbstrakPemanasan global merupakan permasalahan umum yang terjadi di seluruh belahan dunia yang memicu terjadinya perubahan iklim yang cukup signifikan seperti kenaikan suhu, perubahan kelembaban, bencana alam, dan dapat menyebabkan kepunahan flora dan fauna, salah satunya burung walet di Karst Ciampea, yang sudah mengalami kerusakan sehingga tidak layak huni. Selain itu, eksploitasi gua kapur oleh manusia menyebabkan walet merasa tidak nyaman dan diperlukannya habitat buatan. Tujuannya agar kebutuhan walet akan habitat pengganti terpenuhi sehingga ekosistem Karst Ciampea tidak terganggu. Bentuk arsitektur yang dihasilkan berupa penangkaran berbasis teknologi yang mengambil walet sebagai subjek utama proyek. Metode yang digunakan berawal dari fenomena dan urgensi walet yang terjadi di kawasan Karst Ciampea. Kemudian dianalisa dan dihasilkan ide berupa penangkaran. Tetapi, tidak hanya berbatas pada penangkaran, tersedia juga ruang interaksi untuk menusia yang berupa galeri-galeri walet, sehingga pengunjung dapat memandang kehidupan walet. Bentuk bangunan keseluruhan didasarkan pada studi analisa bentuk gerakan terbang walet, sehingga bangunan mengadaptasi banyak bentuk lengkungan yang leluasa sesuai dengan aktivitas keseharian walet. Untuk metode penangkaran, diawali dengan menggunakan teknik adaptasi terlebih dahulu, yaitu dengan menangkarkan burung seriti yang mengasuh telur walet yang diambil dari gua-gua kapur Karst Ciampea. Selain metode dalam perancangan, penggunaan teknologi pada material bangunan terutama penangkaran dan galeri juga banyak menggunakan bahan alami seperti kayu dan dinding bata ekspos yang bersifat alami. Sehingga, untuk menampilkan sisi ‘melampaui ekologi’, tidak hanya terbatas pada ekologi dalam penggunaan material, tetapi terdapat ruang interaksi yang tidak langsung antara manusia dengan walet berfungsi untuk melawan sikap antroposentris manusia, sekaligus membantu manusia untuk turut merasakan kehidupan walet dalam suatu bangunan arsitektur.